2018
DOI: 10.1016/j.celrep.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Lysine Homocysteinylation Induced by High-Fat Diet Suppresses DNA Damage Repair

Abstract: Highlights d High-fat diet induces colonic lysine homocysteinylation (K-Hcy) catalyzed by MARS d Increased MARS copy number is a risk factor for human colorectal cancer (CRC) d K-Hcy impedes DNA damage repair in CRC d K-Hcy inhibition decreases high-fat-induced oncogenic effects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 49 publications
0
79
1
Order By: Relevance
“…Zhang et al [6] treated NE4C cells with 0.1, 0.5, and 1 mM Hcy, and found that the pathological effects of Hcy were in a dose-dependent manner. In our previous study of DNA damage model induced by hydroxyurea, we have observed that supplementing the cell-culture media with 0.5 mM Hcy aggravated the number of damaged cells in HCT116 cells [35]. Therefore, we used 0.5 mM Hcy to observe its effects on accumulation of DNA damage and promotion of cytotoxicity in NE4C cells under conditions of MMCinduced DNA damage in this study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Zhang et al [6] treated NE4C cells with 0.1, 0.5, and 1 mM Hcy, and found that the pathological effects of Hcy were in a dose-dependent manner. In our previous study of DNA damage model induced by hydroxyurea, we have observed that supplementing the cell-culture media with 0.5 mM Hcy aggravated the number of damaged cells in HCT116 cells [35]. Therefore, we used 0.5 mM Hcy to observe its effects on accumulation of DNA damage and promotion of cytotoxicity in NE4C cells under conditions of MMCinduced DNA damage in this study.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have been shown that Hcy can sensitize cells to DNA damage agents [15,35]; however, the precise mechanism by which Hcy exacerbates DNA damage in neural cells is not fully discovered. Mitomycin C (MMC), a common chemotherapeutic drug for many malignancies, inhibits cell proliferation and causes death by inducing ICLs [36][37][38].…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting epidemiological evidence indicates that HFDs, rich in carbohydrates and saturated fatty acids, are an acknowledged risk factor for CRC 42 . HFDs lead to commensurate increases in fecal bile acids, particularly lithocholic and deoxycholic acids, which are potent inducers of CRC 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, certain ARSs and AIMPs could regulate tumorigenesis by p53 ( Park et al, 2005 ; Choi et al, 2011 ; Wang et al, 2018 ). High-fat diet induced colonic lysine homocysteinylation through MRS, which led to the accumulation of DNA damage and colorectal cancer-like phenotypes in the colon of mice and rats ( Wang et al, 2018 ).…”
Section: Roles Of Arss In Cancermentioning
confidence: 99%